Chemopreventive effect of ethanolic extract of Gynura procumbens (Lour), Merr on the carcinogenesis of Rat breast cancer development - Meiyanto, Edy; Susilowati, Sri; Tasminatun, Sri; Murwanti, Retno; ., Sugiyanto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Gynura procumbens (Lour) Merr., empirically, used to prevent cancer development and has been proven to be able to suppress lung cancer development. The aim of this research is to examine the potential of ethanolic extract of G. procumbens to suppress DMBA-induced breast cancer development. Sprague Dawly Rats were used in this research and were grouped as indicated treatment. Ethanolic extract of G. procumbens was administered into 3 levels of doses, namely 250, 500, and 750 mg/kgBW. Tumor development was examined by palpation every week and terminated at week 16th after the end of DMBA treatment. The result showed that extract treatment at the dose of 250, 500, and 750 mg/kgBW reduced tumor incidence by 60%, 30 %, and 20 % respectively. The doses of 500 and 750 mg/kgBW exhibited strong suppression of tumor multiplicity, where as the dose of 250 performed less potential suppression. In conclusion, ethanolic extract of G. procumbens performs chemopreventive effect to suppress breast cancer development at the dose of 250 mg/kgBW.Key words : chemopreventive, Gynura procumbens (Lour) Merr, breast cancer.